Acute toxicity reduction and toxicity identification in pigment-contaminated wastewater during anaerobic-anoxic-oxic (A/A/O) treatment process. (February 2017) - Deng, Minjie; Zhang, Ying; Quan, Xie; Na, Chunhong; Chen, Shuo; Liu, Wei; Han, Shuping; Masunaga, Shigeki
Abstract: In China, a considerable part of industrial wastewater effluents are discharged into the municipal wastewater treatment plants (WWTPs) after pretreatment in their own wastewater treatment plants. Even though the industrial effluents meet the professional emission standards, many micro-pollutants still remained, and they could be resistant in the municipal WWTPs with conventional activated sludge process. Pigment wastewater was chosen in this study, and the acute toxicity reduction and identification of the pigment-contaminated wastewater treated by the conventional anaerobic-anoxic-oxic (A/A/O) process were evaluated. Results indicated that the raw pigment-contaminated wastewater was acutely toxic to Photobacterium phosphoreum ( P. phosphoreum ), Daphnia magna ( D. magna ) and Danio rerio ( D. rerio ). The acute toxicity was decreased in some degree after A/A/O treatment, but the final effluent still exhibited acute toxicity to D. magna and D. rerio with the toxic units (TU) of 1.1 and 2.0, respectively. Chemical analyses showed the presence of various refractory and toxic nitrogen-containing polycyclic and heterocyclic compounds in the pigment-contaminated wastewater. Toxicity identification by combining chemical analyses and correlation analysis showed that N-containing refractory organic toxicants were the main toxicity source for the pigment-contaminated wastewater, and several toxicants showed significant correlation with P. phosphoreum and D. magna . This study indicated that the A/A/O process was not efficient for pigment-contaminated wastewater treatment, and it was irradiative for technology improvement in the WWTPs receiving pretreated industrial wastewater effluents. Highlights: The raw pigment-contaminated influent showed acute toxicity. The final effluent through A/A/O process still showed acute toxicity to D. magna and D. rerio. A mass of N-containing toxicants were detected in the pigment-contaminated wastewater. Semi-quantitatively analysis of 9 specific toxicants was performed with GC-MS. N-containing refractory toxicants were identified as the major acute toxicity source.